Physicians’ and nurses‘ knowledge and attitudes in management of sepsis: An Italian study - Gabriella Nucera; Anna Esposito; Naomi Tagliani; Chiara Jane Baticos; Pietro Marino (Journal of Health and Social Sciences)
Introduction: Sepsis is one of the most deadly and costly conditions at hospitals. Our study aimed to study levels of knowledge and attitudes in management of sepsis among nurses and physicians employed at Fatebenefratelli hospital, Milano, North-Italy, with particular regard to the analysis of the effects of educational training. Methods: A cross-sectional, quasi-experimental study was conducted between June 1 and October 30, 2017. Physicians and nurses from Intensive Care Unit (ICU) and non-ICU hospital wards were recruited. The study participants were invited to attend some educational workshops and, after 6 months, to fill out a questionnaire based on the 2016 Surviving Sepsis Campaign guidelines. Descriptive statistics were expressed with frequency and percentage (%). Chi-square and Student’s t-test were performed to compare the differences in awareness and knowledge between groups. P-values < 0.05 were considered statistically significant. Results: Nurses and physicians reported both ‘good’ levels (> 75%) of knowledge of procedures that increase risk of sepsis, ‘fairly‘ (50-75%) levels of knowledge, attitudes and behaviour towards blood culture techniques, and ‘poor’ (< 50%) levels of knowledge concerning early identification, methods and scores for diagnosis and management of sepsis. However, with regard to this latter point, T Student test for sample independent confirmed a significant difference in the average percentages of correct answers between recently (~ 6 months) trained (74 ± 3.4%) nurses (n = 33) and physicians (n = 19) and not recently (> 1 years) or never trained (34.8 ± 7.4%) nurses (n = 99) and physicians (n = 30) (t(10) = 11.72, P = < 0.001). Discussion and Conclusion: Our findings showed that levels of knowledge concerning methods and scores for early identification of sepsis can be significantly improved by educational training. A good knowledge of sepsis guidelines is essential to correct management of this condition.